Pengaruh Kecepatan Laju Aliran Gas Pelindung Pengelasan Gmaw Pada Baja Karbon Rendah Terhadap Hasil Pengujian Tekan - Manahan Hutagalung (JURNAL VOKASI TEKNIK, 2024)
One of the welding methods that is often used by the general public includes welding steel pipes, namely the GMAW (Gas Metal Arc Welding) method. This welding is also called MIG because it uses inert gas where the electrodes used are not coated and can supply continuously, because they are in the form of rolls. good weld results, one of which is the speed of flow of the shielding gas and the shape of the seam. This research uses an experimental method by varying the flow speed of the protective gas in pipe welding, namely 10 liters/min, 20 liters/min, 25 ltr/min. Of the three specimens that have been compressed tested, the specimen with a protective gas flow speed of 10 liters/min is of 0.47 Mpa, at a protective gas flow rate of 20 liters/min it is 0.49 Mpa, and at a protective gas flow rate of 25 liters/min it is 0.49 Mpa.